ELL’s science meaning making in multimodal inquiry: a case-study in a Hong Kong bilingual school - Williams, Melanie; Tang, Kok-Sing; Won, Mihye (SpringerOpen, 2019)
This paper reports on a multimodal teaching approach delivered to grade 5 elementary students in a bilingual school in Hong Kong, as part of a larger research study aimed at supporting English Language Learners (ELLs) in science class. As language demands of reading, writing and talking science place additional challenges on ELLs, there is much research interest in exploring the use of multiple modes of communication beyond the dominant use of verbal and written language. Research has shown that students develop a better scientific understanding of natural phenomena by using and alternating between a variety of representations. Yet, questions remain as to what meanings ELLs make during a multimodal discourse and, in turn, how such discourse provides support to ELLs in learning science. Drawing on social semiotics, which theorizes language as a meaning making resource comprising a range of modes (e.g. gestures and diagrams), we used a case-study approach to examine how a multimodal instructional approach provided 10 students with multiple avenues to make sense of science learning. Video recordings (capturing gestures, speech and model manipulation) and student works (drawing and writing) were collected during nine inquiry science lessons, which encompassed biology, physics and chemistry science units. Multimodal transcription allowed discourse to be analysed at a fine-grain level which, together with analysis of student works, indicated that the multimodal instructional approach provided the necessary inquiry opportunities and variety of language experiences for ELLs to build science understandings. Analysis also revealed how the affordances of modes attributed to the meaning making potentials for the ELLs and how they provided alternate communication avenues in which new meanings could be made. The findings from this study have implications for ELLs learning science within the growing multilingual Asia-Pacific region.